Effect of projected sea level rise on the hydrodynamic and suspended sediment concentration profile of tropical estuary - Mohd Salleh, Shahirah Hayati; Ahmad, Anizawati; Wan Mohtar, Wan Hanna Melini; Lim, Chai Heng; Maulud, Khairul Nizam Abdul (Elsevier, 2018)
Kuala Pahang, an estuary located in the East Coast of Malaysia is projected to experience a 0.03, 0.14 and 0.31 m increase in sea level in the years 2020, 2060 and 2100, respectively. To predict how tide and current speed affect suspended sediment concentration, the MIKE 21 HD and ST models were used to simulate the hydrodynamics and sediment transport at Kuala Pahang. The study is limited to the Southwest Monsoon period and the model was conducted as a localised analysis at the Kuala Pahang estuary. The results of hydrodynamic modelling of 2014 baseline showed the difference in water level between spring and neap tide had influenced the current speed as the maximum flow velocity varies between 0.20 and 1.95 m/s. The Southwest Monsoon affects current flow in two ways, namely through the sea dominated flood tide and through river discharge during ebb tide. Meanwhile rising in sea level had increased 10% of the current speed in year the 2060 based on the 2014 model. Sediment transport modelling showed that the averaged suspended sediment concentration (SSC) fluctuated between 55–1532 mg/l in the year 2014 and could reach a maximum value up to 5091 mg/l in the year 2100, even with an increment of only 0.10 m/s maximum current speed. The profound impact of SLR on hydrodynamics and SSC is significant at the Kuala Pahang estuary and has a direct impact on the socio-economic and livelihood of local communities. This projection model can provide an effective management for the sustainability of estuary ecosystem and is relevant for understanding future hydrodynamic and suspended sediment patterns.